Strategi Pengumpulan dan Pendistribusian Zakat, Infak dan Sedekah untuk Kesejahteraan Umat: Studi Komperatif antara LAZ-UQ dengan LAZISNU Jombang: Strategi Pengumpulan dan Pendistribusian Zakat, Infak dan Sedekah untuk Kesejahteraan Umat: Studi Komperatif antara LAZ-UQ dengan LAZISNU Jombang - Pramiswari, Riris; Amarudin, Amin Awal; Mustamim, Mustamim (Journal of Islamic Law, 2021)
The high potential of Zakat, Infāq, and Alms (ZIS) in the Jombang Regency is not under the funds collected. This matter has resulted in many poor people in Jombang Regency. This paper explores the strategy of raising funds and distributing ZIS in two institutions, namely the Lembaga Amil Zakat Ummul Quro (LAZ-UQ) and the Lembaga Amil Zakat, Infak, Sedekah Nahdlatul Ulama (LAZISNU) Jombang. This study is a comparative study with a qualitative approach and uses observation and interviews as data collection techniques. The results showed three similarities in the collection of ZIS funds between ZIS at LAZ-UQ and LAZISNU Jombang, namely the separation between zakat funds and infāq, socialization through social media, and collaborating with several institutions. The difference is that LAZ-UQ relies more on fund transparency reports through bulletins and various program variations. In contrast, LAZISNU relies on socialization through recitations and mobilizing institutions under Nahdlatul Ulama. The author found that the variation of the LAZ-UQ program was more varied than that of LAZISNU Jombang from the aspect of the distribution of ZIS funds. LAZ-UQ carries out programs for providing business capital, sales groups, building stalls, the Independent Livestock Center program, Griya Orphans, and the Mandiri Prosperous Capital Program. Meanwhile, LAZISNU distributed ZIS funds through the qard hasan (productive) program, compensation to the poor, orphans, and widows, and paying off the interest on loans from small traders who owed moneylenders (consumptive). Although they differ in the collection and distribution of ZIS funds, the two institutions have the same goal of increasing the welfare of mustahik.